Pengolahan Limbah Kulit Durian (Durio Zibethinus Murray) Sebagai Adsorben pada Penyerapan Ion Logam Berat Pb2+ - Husein, Saddam; Nasra, Edi (Periodic, 2025)
The contamination of water bodies by lead ions (Pb2+) from industrial waste represents a severe environmental challenge due to the metal’s toxicity, bioaccumulation, and no-biodegradable nature. This study investigates the synthesis and application of activated carbon and silica xerogel derived from durian husk waste (Durio zibethinus Murray) for Pb2+ adsorption. The synthesis involved extracting karbon and silika xerogel through thermal and chemical treatments. Characterization by X-Ray Fluorescence (XRF) results showed the silica content in durian husk is 31,1% and characterize with Fourier Transform Infra Red (FTIR) to determine functional group of the adsorbents. Adsorption process indicated that pH strongly influenced Pb2+ removal with optimal performance at pH 3 for activated carbon with adsorption capacity of 14,95 mg/g and at pH 5 for silica.